The Effect of Online Promotion on the Decision to Purchase Airline Tickets with the Digital Era as a Mediating Variable in E-Ticketing Applications - Silvia Choirun Nissa; Ihwan Susila (International Journal of Economics, Commerce, and Management, 2025)
This study explores in greater depth the effect of online promotions on airline ticket purchasing decisions through e-ticketing applications, emphasizing the mediating role of the digital era. Adopting a quantitative research design, data were collected from 491 respondents who had experience purchasing airline tickets via leading digital platforms such as Traveloka, Tiket.com, Agoda, and Booking.com. Five core online promotional strategies were investigated—discounts and vouchers, email marketing, social media promotions, influencer marketing, and push notifications—each representing distinct digital touchpoints. Partial Least Squares (PLS) analysis was used to test the relationships among variables and to evaluate the mediating effect of the digital era. The results indicate that all five promotional strategies significantly influence purchasing decisions, with influencer marketing and social media promotions emerging as the strongest drivers of consumer behavior. Furthermore, the digital era was shown to enhance consumer trust, accessibility, and engagement, thereby strengthening the impact of online promotions on purchase decisions. These findings highlight the need for airlines and e-ticketing platforms to develop integrated digital marketing strategies that align with evolving consumer behaviors and technological trends. This research contributes to the growing body of literature on digital marketing in the aviation sector and provides practical recommendations for optimizing promotional effectiveness.